THE USE OF DIRECT INSTRUCTION METHOD TO IMPROVE THE ABILITY OF TYING LACED SHOES IN DOWN SYNDROME CHILD CLASS IV IN SLB THERESIA SONDER - YUDIT TRININGSIH; MARIA WANTAH; Aldjon Nixon Dapa (Journal of Disability, 2022)
The purpose of this study was to determine whether the use of the direct instruction method could improve the self-development ability to tie shoes with laces for children with Down syndrome. The research method used is the Single Subject method. this was held at SLB Theresia Sonder. With the subject of class IV students totaling 1 person, as for the data collection techniques (observation and tests). The results showed that the direct instruction method could improve the self-development ability to tie lace-up shoes in children with Down syndrome at Theresia Sonder Special School. Therefore, the use of this method will greatly affect the improvement of the results of students' abilities.